2021
DOI: 10.54530/jcmc.275
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude and Practice Towards Prevention of Covid-19 Among Undergraduate Medical College Students

Abstract: Background: COVID-19 pandemic is a public health burden and threat all around the world. Good Knowledge, Attitude and Practice towards prevention can break the chain of transmis­sion. The study aimed to assess the knowledge, attitude and practice towards prevention of COVID-19. Methods: This was a cross sectional study conducted during 5th to 28th of October 2020 among undergraduate Medical College students. An online questionnaire was developed using Google Forms. The mean knowledge, attitude, and practice of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…This is in line with a study conducted in Saudi Arabia, 22 which clarified that the study participants reported a balance between inactive and proactive practices about COVID-19 (44.6% vs 55.4% respectively). Conversely, the percentage is slightly different from other studies, 26 , 27 that revealed that around two-thirds of the study population (73.4%, and 74.8% respectively) had a high and moderate practice score level. On the other side, a minority of students showed a good or satisfactory practice level in different studies in Egypt (7.0%), 20 Saudi Arabia (5.6%), 21 and Bangladesh (39.5%).…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…This is in line with a study conducted in Saudi Arabia, 22 which clarified that the study participants reported a balance between inactive and proactive practices about COVID-19 (44.6% vs 55.4% respectively). Conversely, the percentage is slightly different from other studies, 26 , 27 that revealed that around two-thirds of the study population (73.4%, and 74.8% respectively) had a high and moderate practice score level. On the other side, a minority of students showed a good or satisfactory practice level in different studies in Egypt (7.0%), 20 Saudi Arabia (5.6%), 21 and Bangladesh (39.5%).…”
Section: Discussioncontrasting
confidence: 90%
“…The study revealed that older students significantly had higher KAP scores in comparison with younger ones with a similar result in a cross-sectional study conducted in Bangladesh. 28 But this disagrees with other studies in Nepa, 26 and India, 29 which clarified that there was no statistically significant difference in knowledge score regarding the age of participants. This can be explained by the fact that older students had work experience and consequently better knowledge about the disease.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations